Precision Medicine: IL-1RA and Pancreatic Cancer Organoids - Annah G. Morgan; Michelle F. Griffin; Michael T. Longaker; Jeffrey A. Norton (Biology)
Cancer organoids have emerged as transformative models for studying tumor biology and therapeutic responses due to the ability to replicate the complexity of the tumor microenvironment (TME). Tumor organoids recapitulate the genetic and phenotypic diversity of cancers, making them invaluable for investigating mechanisms of resistance and identifying novel therapeutic targets. Patient-derived organoids (PDOs) allow specific treatment methods to be designed based on the properties of each individual tumor in vitro. Pancreatic ductal adenocarcinoma (PDAC) is an aggressive cancer with an immunosuppressive nature. PDAC has a poor prognosis, with the survival rates of metastatic PDAC being improved only minimally over the last few decades. In this study, we demonstrate the antitumor effects of an IL-1 receptor antagonist (IL-1RA) in murine and human PDAC organoids. By reducing the burden of suppressive tumor elements like CAFs, IL-1RA treatment facilitates better immune cell access and response.